Fractal statistics of brittle fragmentation (Fracture and Structural Integrity, 2013)
The study of fragmentation statistics of brittle materials that includes four types of experiments is presented. Data processing of the fragmentation of glass plates under quasi-static loading and the fragmentation of quartz cylindrical rods under dynamic loading shows that the size distribution of fragments (spatial quantity)is fractal and can be described by a power law. The original experimental technique allows us to measure, apartfrom the spatial quantity, the temporal quantity - the size of time interval between the impulses of the lightreflected from the newly created surfaces. The analysis of distributions of spatial (fragment size) and temporal(time interval) quantities provides evidence of obeying scaling laws, which suggests the possibility of selforganized criticality in fragmentation.
Keywords: Fragmentation of brittle materials; Fractal statistics